Optimizing Tsunami Evacuation Route with GIS and Network Analysis: Case Study of Barus City, Central Tapanuli, Indonesia - Sahputra, Erry; Basid, Abdul; Sirait, Ratni; Lubis, Lailatul Husna (UIR PRESS, 2026)
A tsunami is a natural disaster triggered by the vertical displacement of the seafloor following a major earthquake along a megathrust zone. Barus District lies within the active Sumatran megathrust, making it highly vulnerable to large earthquakes that could generate tsunamis. This study aims to map tsunami hazard and risk zones under a 16-meter wave scenario and to model evacuation routes using Geographic Information Systems (GIS) and Remote Sensing approaches. The research employs a descriptive quantitative method, integrating spatial data through overlay and network analysis techniques. The analysis revealed that high-hazard and high-risk zones each cover 0.64 km² out of the total 2.27 km², primarily located in Pasar Terandam and Pasar Batu Gerigis villages. Evacuation route modeling showed estimated travel times ranging from 25.06 to 65.73 minutes, assuming an average walking speed of 1.2 m/s. Among the designated shelters, the Catholic church offers a more efficient route, whereas evacuation to the HKBP church requires more than 60 minutes exceeding the ideal time limit. These findings highlight the urgent need to prioritize disaster mitigation strategies to ensure the effectiveness of tsunami evacuation systems in high-risk coastal areas.